Voluntary Partnership Agreements: Assessing impacts for better policy decisions - Cerutti, P.O.; Goetghebuer, T.; Leszczynska, N.; Dermawan, A.; Newbery, J.; Tabi Eckebil, P.P.; Tsanga, R. (Elsevier, 2021)
The European Union's Forest Law Enforcement, Governance and Trade (FLEGT) Action Plan is an ambitious strategy to fight illegal logging and its negative impacts. The FLEGT theory of change is based on three types of FLEGT actions, namely timber production, demand, and global timber trade standards and dynamics. FLEGT works in more than a dozen countries through Voluntary Partnership Agreements (VPA). Very few studies exist on the global or country-level impact of the FLEGT-VPA process. We sought to understand the contribution of FLEGT-VPAs in three countries (Cameroon, Ghana, and Indonesia) at different stages of VPA implementation. A uniform methodology was applied to provide cross-cutting results on perceived changes directly linked to the FLEGT expected impacts while allowing for contextual specificities. This approach is designed to be easily replicable in all VPA countries and directly linked to the FLEGT global theory of change. This commentary presents our findings and their implications for policy makers.